The genotypic and family characteristics and clinical intervention of neurofibromatosis type 1 gene are associated with dystrophic scoliosis by whole-exome sequencing - Du, Yukun; Bai, Tianyu; Song, Jie; Zhang, Li; Huang, Hui; Han, Peng; Gai, Fangfang; Guo, Jianwei; Li, Jianyi; Lv, Changlin; Shao, Jiale; Zhang, Guodong; et al. (Frontiers in Neurology, 2025)
BackgroundTo investigate the genotypic and family genetic characteristics of neurofibromatosis type 1 (NF-1) patients associated with dystrophic scoliosis and to further evaluate the clinical efficiency of surgical intervention to these patients.MethodsA total of seven NF-1 patients with dystrophic scoliosis and their 11 immediate relatives were included in this study who visited The Affiliated Hospital of Qingdao University spinal surgery department from January 2020 to December 2022. The outcomes were summarized by investigating the clinical and imaging parameters before and after the treatment. Whole-exome sequencing (WES) was conducted to analyze the genotypic and family genetic characteristics of all patients and their families.ResultsAmong the seven patients, six patients underwent surgical treatment after follow-up. Compared to preoperative Cobb angle, the maximum postoperative correction rate was 85.3%. We identified eight pathogenic variants in the NF-1 gene. The variants c.c4084T and c. T4445C were located in the GAP-related domain, and the variant c. G1885A was shared by patient 3 and his diseased sibling. In the family of patient 3, variant c. G1885A was detected in both neurofibromatosis patients. The rs112819846 exhibited the most pronounced frequency disparity, whereas rs2916067 and rs80221306 were found in all patients.ConclusionIn this cohort study, NF-1 patients with dystrophic scoliosis predominantly presented with upper thoracic involvement, and surgical correction achieved a maximum postoperative Cobb angle correction rate of 85.3% without loss of correction during follow-up. The c. G1885A variant in the NF-1 gene may influence the phenotypic severity of the disease, while rs112819846, rs2916067, and rs80221306 may represent disease-relevant pathogenic variants of NF-1 patients with dystrophic scoliosis.